Deletion of the Human Cytomegalovirus US2 to US11 Gene Family Members Impairs the Type-I Interferon Response - Inessa Penner; Nadine Krämer; Julia Hirsch; Nicole Büscher; Hanno Schmidt; Bodo Plachter (Viruses)
Infection of cells with the human cytomegalovirus (HCMV) triggers the expression of interferon-stimulated genes (ISGs). ISGs encode proteins with antiviral functions, such as inhibiting viral replication, promoting cell death of infected cells and enhancing immune responses. HCMV has evolved mechanisms to evade the antiviral effects of ISGs. The viral proteins encoded by the viral genes US7, US8, and US9 have been shown to interfere with interferon induction. US7 to US9 are embedded in a cluster of HCMV genes, termed US2 to US11. The individual members of this gene family interfere on multiple levels with innate and adaptive immune responses to HCMV infection. Using viral mutants with different deletions in US2 to US11, we addressed the question if genes other than US7 to US9 would also influence the IFN responses. Surprisingly, deletion of the complete US2 to US11 gene region led to reduced levels of selected ISGs. Cells infected with viruses in which individual US2 to US11 genes were deleted showed a less pronounced reduction of the selected ISGs. The experiments including RNA-seq analyses indicate that genes of the US2 to US11 gene family have a complex interaction with the IFN-ISG response which is likely regulated on the level of ISG protein stability. As US2–US11 are dispensable for replication in cell culture, the genomic region was frequently used for the insertion of bacterial artificial chromosome vectors in the process of cloning the complete HCMV genome. The results shown here must be considered when viruses derived from BACs with US2–US11 deletions are used and whether appropriate controls must be applied.